TRIMETHOPRIM DETERMINATION WITH DRUG-SELECTIVE ELECTRODES - SARRAA A ABRAHEM; AMINA M ABASS; AHMED AHMED (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Developed ion-selective electrode has been industrialized for the determination of trimethoprim (TMP) in pure form and pharmaceutical preparations. The selective electrode was made from TMP with pairing agent methyl orange presence of o-nitrophenyl octyl ether (o-NPOE) and dibutyl phthalate as the plasticizing solvent mediator. Electrode 1 showed a Nernstian reply with a mean calibration graphs slope of 57.31 mv.decade−1, over the linear concentration range of 6.0×10−6–1.0×10−2 M of the drug, with detection limits 3.0×10−6 M. The electrode was effective at pH range between 2.0 and 5.5 for concentration of 10−2 M, 1.5–4.5 for concentration of 10−2 M, and 3.0–4.5 for concentration of 10−4 M of TMP solutions. The electrode 2 gave a non- Nernstian slope equal to 41.20 mv.decade−1. The influence of interfering species such as inorganic cations was studied. Electrode 1 showed an effective response for a period of 27 days, without important variation in parameters of electrode. The suggested electrode was intended for the determination of TMP in pharmaceutical design and pure formula.